ASSESSMENT OF LIFE INSURANCE SERVICE QUALITY DIMENSIONS AND CUSTOMER SATISFACTION THROUGH THE SERVPERF MODEL - H. Josiah; Prem, Babita (International Journal of Research -GRANTHAALAYAH, 2023)
The present research focused on assessing the life insurance service quality and customer satisfaction through the SERVPERF model. In the wake of Liberalization, privatization, and Globalization (LPG) has significantly impacted the insurance industry in India. This leads to the emergence of private and foreign players in the country. The private and foreign insurance companies established in the country provide effective service using the latest technology. All foreign players operated in India through joint ventures with private players. In this cutthroat competition among life insurance companies, consumers are very much aware of the alternatives available concerning services and the provider organization. Now consumer expectations are rising, and service provider organizations should be aware of these expectations. The present study's objective is to compare and analyze the service quality perception of customers about public and private sector life insurers through the SERVPERF model. A total of 400 respondents completed the field survey conducted in Chennai city. Out of 400 respondents, 100 were from LIC, and the rest 300 respondents were from private sector life insurance companies of ICICI Prudential, SBI Life, and HDFC Life Insurance Company Limited. The private players have been adopted based on their market share. The collected data are analyzed with the help of SPSS package version 21. Based on the analysis researcher found that both public and private sector life insurers offered quality services to customers equally.